2020
DOI: 10.1111/pops.12689
|View full text |Cite
|
Sign up to set email alerts
|

Googling Politics: How Offloading Affects Voting and Political Knowledge

Abstract: Studies suggest that individuals are less likely to process information they can easily look up. Instead of committing information to memory, they rely on the Internet to store information for them—a phenomenon known as “offloading.” We examine the effects of offloading on political knowledge and voting behavior. Using data from a 10‐wave panel experiment designed to study information processing in two distinct information environments, we demonstrate that people whose environment is conducive to offloading le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…The body of causal evidence on political knowledge looks relatively promising for this relationship, too. Multiple articles found that enhanced engagement with digital media increased political knowledge [64,67,69,71] and that increased engagement with political content on social media increased political interest among adolescents [107]. In line with these findings, it has been reported that political messages on social media, as well as faster download speed, can increase information-seeking in the political domain [64,68].…”
Section: Few Articles Have Shed Light On Causal Effects Between Social Media Use and Trust A Field Experiments In The Unitedmentioning
confidence: 78%
See 2 more Smart Citations
“…The body of causal evidence on political knowledge looks relatively promising for this relationship, too. Multiple articles found that enhanced engagement with digital media increased political knowledge [64,67,69,71] and that increased engagement with political content on social media increased political interest among adolescents [107]. In line with these findings, it has been reported that political messages on social media, as well as faster download speed, can increase information-seeking in the political domain [64,68].…”
Section: Few Articles Have Shed Light On Causal Effects Between Social Media Use and Trust A Field Experiments In The Unitedmentioning
confidence: 78%
“…In our sample, causal analyses of the effects of digital media on political participation in Western democracies mostly studied voting and voter turnout [61,64,68,[71][72][73]; articles concerned with other regions of the world focused on political protest behavior [56,58,63]. Other articles considered online political participation [62,68].…”
Section: Effects On Key Political Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Causal analyses of the effects of digital media on political participation in established democracies mostly studied voting and voter turnout 64,67,71,[74][75][76] ; articles concerned with other regions of the world rather focused on political protest behaviour 59,61,66 . Other articles considered online political participation 65,71 .…”
Section: Effects On Key Political Variablesmentioning
confidence: 99%
“…The former observation of diverse news exposure might fit with the beneficial relationship between digital media and knowledge reported in refs. 67,74,94,95,102 , and the homophilic social structures could be connected to the prevalence of hate speech and anti-outgroup sentiments 120,[152][153][154][155] .…”
Section: Established Democraciesmentioning
confidence: 99%